Functional and structural impact of the most prevalent missense mutations in classic galactosemia. Issue 6 (23rd June 2014) - Coelho, Ana I.; Trabuco, Matilde; Ramos, Ruben; Silva, Maria João; Tavares de Almeida, Isabel; Leandro, Paula; Rivera, Isabel; Vicente, João B.
Abstract Galactose‐1‐phosphate uridylyltransferase (GALT) is a key enzyme in galactose metabolism, particularly important in the neonatal period due to ingestion of galactose‐containing milk. GALT deficiency results in the genetic disorder classic galactosemia, whose pathophysiology is still not fully elucidated. Whereas classic galactosemia has been hypothesized to result from GALT misfolding, a thorough functional–structural characterization of GALT most prevalent variants was still lacking, hampering the development of alternative therapeutic approaches. The aim of this study was to investigate the structural–functional effects of nine GALT mutations, four of which account for the vast majority of the mutations identified in galactosemic patients. Several methodologies were employed to evaluate the mutations' impact on GALT function, on the protein secondary and tertiary structures, and on the aggregation propensity. The major structural effect concerns disturbed propensity for aggregation, particularly striking for the p.Q188R variant, resulting from the most frequent (~60%) allele at a worldwide scale. The absence of major effects at the secondary and tertiary structure levels suggests that the disturbed aggregation results from subtle perturbations causing a higher and/or longer exposure of hydrophobic residues in the variants as compared to WT GALT. The results herein described indicate a possible benefit from introducing proteostasis regulators and/or chemical/pharmacological chaperones to prevent the accumulation of protein aggregates, in new avenues of therapeutic research for classic galactosemia.